Mechanisms responsible for postmenopausal hypertension in a rat model: Roles of the renal sympathetic nervous system and the renin–angiotensin system. Issue 2 (26th January 2016) - Maranon, Rodrigo O.; Reckelhoff, Jane F.
Abstract: Hypertension in postmenopausal women is less well controlled than in age‐matched men. The aging female SHR is a model of postmenopausal hypertension that is mediated in part by activation of the renin–angiotensin system (RAS) and by the renal sympathetic nervous system. In this study, the hypothesis was tested that renal denervation would lower the blood pressure in old female SHR and would attenuate the antihypertensive effects of AT1 receptor antagonism. Retired breeder female SHR were subjected to right uninephrectomy (UNX) and left renal denervation (RD) or UNX and sham, and 2 weeks later, baseline mean arterial pressure (MAP; radiotelemetry) was measured for 4 days, and then rats were treated with angiotensin (AT1) receptor antagonist, losartan (40 mg/kg/day po) for 6 days. Renal denervation reduced MAP in old females compared to sham (172 ± 6 vs. 193 ± 6 mm Hg; P < 0.05). Losartan reduced MAP in both sham and RD rats similarly (numerically and by percentage) (142 ± 10 vs. 161 ± 6 mm Hg; P < 0.05 vs. RD, P < 0.05 vs. baseline). However, female SHR rats remained significantly hypertensive despite both pharmacological intervention and RD. The data suggest that both the renal sympathetic nervous system and the RAS have independent effects to control the blood pressure in old female SHR. Since the denervated rats treated with losartan remained hypertensive, the data also suggest that other mechanisms than the RAS and renal sympathetic nervous system contribute to the hypertension in old female SHR. The data also suggest that multiple mechanisms may mediate the elevated blood pressure in postmenopausal women. Abstract : Renal denervation reduces blood pressure in old female SHR (aged 16 months) by approximately 20 mm Hg. Treatment with losartan, the angiotensin II AT1 receptor antagonist, lowered blood pressure further, suggesting that both the renal nerves and teh renin‐angiotensin system contribute independently to the elevated blood pressure in the old females. The data suggest that multiple mechanisms may also be responseible for postmenopausal hypertension in women.